2019
DOI: 10.2147/ccid.s205904
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of a cream containing 5% hyaluronic acid mixed with a bacterial-wall-derived glycoprotein, glycyrretinic acid, piroctone olamine and climbazole on signs, symptoms and skin bacterial microbiota in subjects with seborrheic dermatitis of the face</p>

Abstract: Objective: A new cream formulation containing hyaluronic acid 5%, complexed with a mix of a bacterial-wall-derived glycoprotein and peptide glycan complex (EDS), has been recently developed. We evaluated in a prospective, assessor-blinded, 6-week study the efficacy and tolerability of EDS in the treatment of facial seborrheic dermatitis (SD) and the effects on skin microbiota. Subjects and methods: Seventy-five subjects (mean age 46; 60 men) with moderate-severe SD of the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Because Staphylococcus spp and Cutibacterium acnes are considered to be dominant but reciprocally inhibit each other. [22] Early literature showed that the majority of S epidermidis strains also were able to…”
Section: This Is Consistent With the Results Of Souvik Mukherjee Et Al's Andmentioning
confidence: 99%
“…Because Staphylococcus spp and Cutibacterium acnes are considered to be dominant but reciprocally inhibit each other. [22] Early literature showed that the majority of S epidermidis strains also were able to…”
Section: This Is Consistent With the Results Of Souvik Mukherjee Et Al's Andmentioning
confidence: 99%
“…[ [167][168][169][170][171][172] Red Ginseng Reported dual regulation of oxidative stress and increases in Bifidobacteria and Akkermansia gut bacteria. [173] Limosilactobacillus fermentum strains Supplementation with the probiotic mix reduced both inflammation and oxidative stress.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…The severity of the itch was based on the description of the medical records. For each item, a 4grade scale was used (0 = absent, 1 = mild, 2 = moderate, 3 = severe) (11).…”
Section: Subjective Evaluation By Investigator Global Assessment and Patient's Self-assessmentmentioning
confidence: 99%
“…Metronidazole is anti-inflammatory via inhibition of free radical species (9,10). Hyaluronic acid is a naturally occurring, highly conserved polysaccharide (11); it can trigger built-in immune defense mechanisms and promote cytokine production. Biological interactions of hyaluronic acid include effects on cell proliferation, recognition, and locomotion, along with angiogenesis and inflammatory cell activity (12).…”
Section: Introductionmentioning
confidence: 99%